PANDANGAN INOVASI KULINER MASA KINI DALAM PSIKOLOGI SOSIAL DIBIDANG KEWIRAUSAHAAN - Adinda Rokhimatul Fatikhah; Dona Sephia Selawati, Agrefina Damayanti Siahaan, Nur Haliza Putri Rahmad, Sulistiasih (Jurnal Ekonomi dan Bisnis, 2024)
This journal was created to educate and evaluate the world of entrepreneurship in terms of social psychology. Social psychology is the study of how individuals are influenced by their social environment, including their interactions with others, social norms, and existing social situations. Social psychology covers various aspects, one of which is in the field of entrepreneurship. Psychology in the field of entrepreneurship is a development of industrial and organizational psychology. In running entrepreneurship, one of the important factors is the characteristics of the entrepreneur and the problems he faces so that it will lead to innovation in business. Innovation in the culinary field will never end especially in the digital era like today. Creativity and innovation in the culinary business will have an impact on the psychology of consumers who will be interested in trying the culinary.